PENGARUH JOB DESCRIPTION, KOMPETENSI, DAN KOMPENSASI TERHADAP KINERJA APARATUR SIPIL NEGARA INSPEKTORAT KOTA BUKITTINGGI - Aprileny Aprileny; Anne Putri; Aries Tanno (Pascasarjana Universitas Riau Kepulauan, 2021)
The purpose of this study was to see the effect of job description, competence, and compensation on the performance of the State Civil Apparatus at the Bukittinggi City Inspectorate. This type of research is descriptive quantitative with the population is all employees of the ASN Inspectorate of the city of Bukittinggi, in order to obtain a sample of 37 people with a sampling technique. Primary data sources by distributing questionnaires according to the criteria. The data analysis technique used is to test the validity and reliability with Smart-PLS software, then descriptive analysis is carried out to see the level of achievement of the respondents (TCR). The results showed that 1) Job description had a positive and insignificant effect on the performance of the State Civil Apparatus Inspectorate of Bukittinggi city. 2) Competence has a positive and significant effect on the performance of the State Civil Apparatus Inspectorate of Bukittinggi city. This means that the higher the competence of the employee, the better the performance will be. 3) Compensation has a positive and insignificant effect on the performance of the State Civil Apparatus Inspectorate of Bukittinggi.